2016
DOI: 10.1038/ncomms13685
|View full text |Cite
|
Sign up to set email alerts
|

EZH1 and EZH2 promote skeletal growth by repressing inhibitors of chondrocyte proliferation and hypertrophy

Abstract: Histone methyltransferases EZH1 and EZH2 catalyse the trimethylation of histone H3 at lysine 27 (H3K27), which serves as an epigenetic signal for chromatin condensation and transcriptional repression. Genome-wide associated studies have implicated EZH2 in the control of height and mutations in EZH2 cause Weaver syndrome, which includes skeletal overgrowth. Here we show that the combined loss of Ezh1 and Ezh2 in chondrocytes severely impairs skeletal growth in mice. Both of the principal processes underlying gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
81
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 44 publications
6
81
1
Order By: Relevance
“…Complete knockout of EZH2 in mice produced nonviable embryos with abnormal accumulation of mesodermal cells . EZH2 also has key roles in skeletal development as conditional loss of EZH2 , affects skeletal patterning as well as skeletal growth and bone formation . For example, conditional loss of EZH2 in neural crest–derived tissues (using the Wnt1‐Cre driver) causes craniofacial defects .…”
Section: The Basics Of Epigeneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete knockout of EZH2 in mice produced nonviable embryos with abnormal accumulation of mesodermal cells . EZH2 also has key roles in skeletal development as conditional loss of EZH2 , affects skeletal patterning as well as skeletal growth and bone formation . For example, conditional loss of EZH2 in neural crest–derived tissues (using the Wnt1‐Cre driver) causes craniofacial defects .…”
Section: The Basics Of Epigeneticsmentioning
confidence: 99%
“…However, EZH1 partially compensates for loss of EZH2 during skeletal development. Dual inactivation of EZH1 and EZH2 in chondrocytes delays skeletal growth . The most dramatic skeletal phenotypic changes were observed in mice with a conditional null mutation in EED, a scaffolding protein that is required for PRC2 complexes that contain either EZH1 or EZH2 as active enzymatic subunits in the sites .…”
Section: The Basics Of Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently revealed that epigenetic regulation is involved in OA pathology and skeletal growth disorders . Our group recently found that the H3K27 (lysine 27 on histone H3) demethylase KDM6B regulated chondrocyte anabolic metabolism in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblasts trapped in the matrix become osteocytes and the bone‐like material calcifies to form a bone matrix, forming the earliest bone tissue. During cartilage osteogenesis, mesenchymal stem cells aggregate and differentiate into chondrocytes and then the chondrocytes proliferate and secrete cartilage matrix rich in type II collagen and proteoglycans . Under stimulation with certain signals, these cells stop proliferating and enter a state of hypertrophy, secreting a matrix rich in type V collagen.…”
Section: Introductionmentioning
confidence: 99%